Mitologi dalam QS. Al-Kafirun Perspektif Semiotika Roland Barthes - Muhamad Jamaludin; Nur Aini; Ahmad Sihabul Millah (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2021)
The interpretation of Surah al-Kafirun today is found to be a little disturbing for religious people, both among religions and between religious communities. Especially after the largest Islamic organization in Indonesia, namely Nahdatul 'Ulama which issued bahtsul masail results about non-Muslims who are not infidels. Netizens are busy blaspheming and identifying non-Muslims as not even infidels to the point of stating that the meaning of the letter al-Kafirun today is no longer relevant. To answer this question, the author compiles Roland Barthes' theory of semiotics into this letter of al-Kafirun. The author interprets this letter of al-Kafirun using two levels of semiotics. The first level of semiotics analyzes linguistics or language. Meanwhile, the second level semiotics analyzes the connotative meaning in the text by revealing the mythical characteristics of the verse as stated in Roland Barthes' semiotic theory.